2021
DOI: 10.3390/ijerph18137133
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Safety, and Satisfaction of Combined Hysterectomy with Bilateral Salpingo-Oophorectomy and Chest Surgery in Transgender and Gender Non-Conforming Individuals

Abstract: The demand for masculinizing breast surgery and hysterectomy with bilateral salpingo-oophorectomy (HBSO) from transmen has increased. With a multidisciplinary approach, these surgeries can be performed in a single session. The objective of this study was to retrospectively evaluate the feasibility, safety, and satisfaction of HBSO and chest surgery in transmen. A cohort of 142 subjects who underwent HBSO alone or combined with chest surgery at Sant’Orsola Hospital was analyzed. Intra and post operation events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…A total of 17 380 records were identified from the search, with 286 studies 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ...…”
Section: Resultsmentioning
confidence: 99%
“…A total of 17 380 records were identified from the search, with 286 studies 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ...…”
Section: Resultsmentioning
confidence: 99%
“…[42][43][44] Hysterectomy with bilateral salpingo-oophrectomy procedures have shown to have even lower complication rates of 5.3%. 42 Comparatively, a vaginoplasty has been shown to have complication rates between 20% and 70%. 45,46 Similarly, studies have found vulvoplasties, commonly performed in place of a vaginoplasty as it is less invasive, to have complication rates of between 35% and 57.1%, with 91.7% of which considered to be minor under the Clavien-Dindo grading system.…”
Section: Discussionmentioning
confidence: 99%
“…Major complications included major infections, hematomas, and tissue proplapse and stenosis. Masculinizing chest surgery has been shown to have a complication rate of between 10.5% and 16.6%, with more than 71.4% being minor complications 42–44 . Hysterectomy with bilateral salpingo-oophrectomy procedures have shown to have even lower complication rates of 5.3% 42 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation